Survey of Motivation on Bima Town People to Participate in Recreational Sports Activities In the New Normal Era - Satriawan, Rabwan; Amar, Khairul; Irawan, Ewan; Fitriani, Ainun; bagus Endrawan, I (Indonesian Journal of Physical Education and Sport Science, 2023)
Study objectives. This study aims to determine the motivation of the people of Bima City to participate in recreational sports activities in Am understand Park in the new normal era. Materials and methods. This research is a quantitative research with a survey approach. The population in this study were all the people of Bima City who were present in recreational sports activities in Am Understanding Park in the new normal era, and the sampling of this study used a random sampling method with a total sample of 150 samples. This research data collection technique using a questionnaire method, using a sports motivation questionnaire instrument. Results. The results showed that the motivation of the people of Bima City to carry out recreational sports activities in the new normal era was high, as evidenced by the percentage of research results showing that 85% of 150 respondents had high motivation, while 15% had moderate motivation, and 0% had low motivation. Conclusion. The conclusion from this research is the motivation of the people of Bima City to do recreational sports activities in the New Normal era is high. Suggestions in this research are for the City Government of Bima to be able to provide space and support community recreational sports activities in various areas of Bima City.